Intra- and Interrater Reliability of Sagittal Spinopelvic Parameters on Full-Spine Radiographs in Adults With Symptomatic Spinal Disorders - Kati Kristiina Kyrölä (Neurospine, 2018)
Background/Aims To evaluate the intra- and interrater reliability (I-IR) of sagittal spinopelvic parameters from digital full-spine plain radiographs with basic software tools in an unselected adult population with degenerative spinal complaints who were evaluated for surgery. Methods Forty-nine adult full-spine digital radiographs were measured twice by 3 independent observers, including an experienced spine surgeon, an experienced radiologist, and a resident orthopedic surgeon. Clinical picture archiving and communication system workstations and software tools were used and landmarks were set manually. The I-IR of the sagittal vertical axis (SVA), pelvic tilt (PT), pelvic incidence (PI), sacral slope (SS), and thoracic kyphosis in T4–T12 (TK) were assessed. Results The intrarater intraclass correlation coefficient (ICC) scores varied from 0.82 to 0.99. The interrater ICC scores ranged from 0.78 to 0.99. The intrarater standard error of measurement (SEM) values for SS, PT, PI, and TK varied from 0.8° to 5.0°, and the interrater SEM values ranged from 2.5° to 6.2°, depending on the parameter and the reading round. The I-IR SEM values for SVA varied from 2.2 to 5.7 mm and from 4.6 to 5.0 mm, respectively. Kappa values were >0.88 for all readers. The intrarater variability was the smallest for the most experienced rater. Conclusion The I-IR of measuring sagittal spinopelvic parameters on digital full-spine images with basic software tools was high. Parameters consisting of several anatomic landmarks were more liable to error. Rater experience had a positive influence on reliability and repeatability. Reader experience should be assessed before accepting measurements for surgical planning and the interpretation of surgical correction during postoperative follow-up.